Non-Hermitian Complementary Acoustic Metamaterials for Imaging Through Skull With Imperfections - Craig, Steven R.; Welch, Phoebe J.; Shi, Chengzhi (Frontiers in Mechanical Engineering, 2020)
High resolution diagnostic ultrasound imaging requires the use of high frequency acoustic transmission deep into the body. However, the presence of high impedance, lossy barriers such as the skull scatters and damps the energy delivered to the targeted region, limiting the usefulness of ultrasound for brain imaging and brain therapies. Non-Hermitian complementary metamaterials (NHCMM) are precisely designed to enable total and bidirectional acoustic transmission through lossy barriers, poising these metamaterials as a useful tool for non-invasive diagnostic brain imaging and brain therapies. Here, we apply NHCMMs to skull surfaces with unique geometries and irregularities to evaluate the performance of NHCMMs under near realistic imaging circumstances. We employ a multi-step imaging process by collecting the initial reflected pressure field caused by an irregular skull region and an initial metamaterial layer that is not perfectly matched, tailor the metamaterial parameters to complement the skull region, and collect a second pressure field with the tumor present. The tumor location is ascertained by calculating the contrast to noise ratio of the higher amplitude backscattered pressure field compared to the rest of the pressure field. Even with the skull irregularities, the imaging information of an acoustic scatterer, in this paper represented as a brain tumor, is preserved through the bilayer and reconstructible despite the scattering effect caused by the skull imperfections. Evaluating the performance of NHCMMs with various defects is critical to understanding its effectiveness for non-invasive neurological procedures and diagnostic imaging; the success of tumor detection through the NHCMM/skull bilayer illustrated in this paper will ideally lead to implementation in ultrasound diagnostics for neurological disorders.